The MERCOSUR Support to Education Sector Program: Integration Approaches and Limitations Regarding the Teacher Education Reforms - Guillermo Ramón Ruiz (FahrenHouse, 2019)
This paper focusses on cross-national comparison regarding regional policies of one of the main aspects of schooling systems: teacher education. From a qualitative point of view, we analyse normative documents and curriculum definitions, in order to generate a typology which allows us to make comparisons among four South American countries. A hermeneutic and theoretical reconstruction is made from the discursive analysis of the data that was recollected. In this article, we point out the logics that operate under the four States, that we take into account which (besides their specific and contextual characteristics) have significant similarities. All of them have high indicators of structural poverty, unequal economic, educational and cultural developments, with serious problems regarding the access to the housing and to the public health. As a result, we analyse the problematic issues that affect political initiatives such as PASEM because of the institutional logics that characterize the national systems of teacher education. These logics limit the intra-regional harmonization programs and their results. We believe that policy transfers studies constitute a prolific area of research to understand the contradictory interests that affect the educational policies in specific contexts.